PACKAGING DESIGN ANALYSIS OF FOOD PACKAGING HOME INDUSTRY DUMPLING NGENES - Ratnasari, Ima; Juraida, Anita; Maharani Suyono, Annisa (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to analyze the design of the packaging of dumplings in the home products industry. Research carried out by the packaging design factors. This study uses a qualitative method to submit data and information on the packaging design based on the theories and literature used. The results of the research that has been done are that the packaging used by the home industry is good enough.